When Does Monetary Policy Sway House Prices? A Meta-Analysis - Dominika Ehrenbergerova; Josef Bajzik; Tomas Havranek (ZBW - Leibniz Information Centre for Economics, 2021)
Several central banks have leaned against the wind in the housing market by increasing the policy rate preemptively to prevent a bubble. Yet the empirical literature provides mixed results on the impact of short-term interest rates on house prices: the estimated semi-elasticities range from -12 to positive values. To assign a pattern to these differences, we collect 1,447 estimates from 31 individual studies that cover 45 countries and 69 years. We then relate the estimates to 39 characteristics of the financial system, business cycle, and estimation approach. Our main results are threefold. First, the mean reported estimate is exaggerated by publication bias, because insignificant results are underreported. Second, omission of important variables (liquidity and long-term rates) likewise exaggerates the effects of short-term rates on house prices. Third, the effects are stronger in countries with more developed mortgage markets and generally later in the cycle when the yield curve is flat and house prices enter an upward spiral.
Keywords: C83; E52; R21; 330; interest rates; house prices; monetary policy transmission; meta-analysis; publication bias; Bayesian model averaging